Genome-wide identification and expression of TIFY family in cassava (Manihot esculenta Crantz) - Zheng, Linling; Wan, Qi; Wang, Honggang; Guo, Changlin; Niu, Xiaolei; Zhang, Xiaofei; Zhang, Rui; Chen, Yinhua; Luo, Kai (Frontiers in Plant Science, 2022)
Plant-specific TIFY proteins serve important roles in the regulation of plant stress responses. In this work, 28 TIFY genes were found in cassava (Manihot esculenta Crantz). Phylogenetic analyses found that cassava TIFY genes could be categorized into four primary groups: JAZ, PPD, ZML, and TIFY, with the JAZ group further broken into five subgroups (JAZ I to JAZ V). The 26 TIFY genes were irregularly distributed across 14 of the 18 chromosomes, and 18 gene pairs were implicated in large-scale interchromosomal segmental duplication events. TIFY gene synteny comparisons between cassava and three other plant species (Arabidopsis, Populus trichocarpa, and rice) uncovered vital information about their likely evolution. TIFY gene expression patterns were validated using qRT-PCR analysis in response to osmotic, salt, and cadmium stress. This comprehensive study lays the groundwork for future research into TIFY family genes in cassava and may be valuable for genetic improvement of cassava and other related species.